2009
DOI: 10.1248/jhs.55.790
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Antibacterial Activity of Fluoroquinolones with Their Sucralfate-complexes against Clinically-isolated Bacteria

Abstract: Oral fluoroquinolones are widely known to form chelate complexes with metal-containing drugs, resulting in inhibition of their intestinal absorption. However, for intestinal sterilization, the concomitant regimen may be a selective and effective strategy due to decreased absorption of fluoroquinolones result in the retainment of antibiotics at the intestine if the mixture still perpetuated antibacterial activity. Therefore, to clarify whether the mixture of fluoroquinolones and sucralfate affects their antibac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…[56] Experimental evidence exists to suggest that sucralfate may promote wound healing for instance in burn wounds. [7] Sucralfate also has antibacterial activity[89] and has been successfully studied in decreasing pain and improving healing after hemorrhoidectomy, in ulceration and erosion of the perineal area, in ulceration of the vagina, in peristomal and perineal dermatoses, in moist desquamation during radiotherapy, in epidermolysis bullosa, and in burns of the second and third degrees. [1011121314151617] In a pilot study, it has shown benefit in full-thickness, venous stasis ulcers not healing after 8 weeks of conventional therapy.…”
Section: Introductionmentioning
confidence: 99%
“…[56] Experimental evidence exists to suggest that sucralfate may promote wound healing for instance in burn wounds. [7] Sucralfate also has antibacterial activity[89] and has been successfully studied in decreasing pain and improving healing after hemorrhoidectomy, in ulceration and erosion of the perineal area, in ulceration of the vagina, in peristomal and perineal dermatoses, in moist desquamation during radiotherapy, in epidermolysis bullosa, and in burns of the second and third degrees. [1011121314151617] In a pilot study, it has shown benefit in full-thickness, venous stasis ulcers not healing after 8 weeks of conventional therapy.…”
Section: Introductionmentioning
confidence: 99%